ASH1L (a histone methyltransferase protein) is a novel candidate globin gene regulator revealed by genetic study of an English family with beta‐thalassaemia unlinked to the beta‐globin locus. (19th July 2016) - Breton, Amandine; Theodorou, Andria; Aktuna, Suleyman; Sonzogni, Laura; Darling, David; Chan, Lucas; Menzel, Stephan; van der Spek, Peter J.; Swagemakers, Sigrid M.A.; Grosveld, Frank; Philipsen, Sjaak; Thein, Swee Lay
Abstract : In 1993, we described an English family with beta‐thalassaemia that was not linked to the beta‐globin locus. Whole genome sequence analyses revealed potential causative mutations in 15 different genes, of which 4 were consistently and uniquely associated with the phenotype in all 7 affected family members, also confirmed by genetic linkage analysis. Of the 4 genes, which are present in a centromeric region of chromosome 1, ASH1L was proposed as causative through functional mRNA knock‐down and chromatin‐immunoprecipitation studies in human erythroid progenitor cells. Our data suggest a putative role for ASH1L (Trithorax protein) in the regulation of globin genes.